1973
DOI: 10.1111/j.1432-1033.1973.tb02889.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Cytoplasmic l‐Glycerol‐3‐Phosphate Dehydrogenase from Rabbit‐Renal‐Adipose Tissue and Its Comparison with the Skeletal‐Muscle Enzyme

Abstract: Cytoplasmic NAD‐linked l‐glycerol‐3‐phosphate dehydrogenase was isolated from rabbit renal adipose tissue in a preparation that was apparently homogeneous by preparative isoelectric focusing and polyacrylamide‐disc‐gel electrophoresis. The adipose tissue and skeletal muscle enzymes were indistinguishable by disc‐gel electrophoresis, immunological comparisons, apparent Km, values for substrates and coenzymes, isoelectric point in preparative isoelectric‐focusing runs, and apparent molecular weight and Stokes ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

1974
1974
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 45 publications
1
4
1
1
Order By: Relevance
“…The Km values obtained for glycerol 3-phosphate at pH9.0 and for dihydroxyacetone phosphate and NADH at pH 8.0 agree with previous estimates (Black, 1966) but the Km value for NAD+ at pH9.0 is significantly lower. There are no other true Km values available in the literature for comparison but the present work is consistent with earlier estimates of apparent Michaelis constants (Young & Pace, 1958;Telegdi & Keleti, 1968;Fondy et al, 1969;Warkentin & Fondy, 1973).…”
Section: Discussionsupporting
confidence: 92%
“…The Km values obtained for glycerol 3-phosphate at pH9.0 and for dihydroxyacetone phosphate and NADH at pH 8.0 agree with previous estimates (Black, 1966) but the Km value for NAD+ at pH9.0 is significantly lower. There are no other true Km values available in the literature for comparison but the present work is consistent with earlier estimates of apparent Michaelis constants (Young & Pace, 1958;Telegdi & Keleti, 1968;Fondy et al, 1969;Warkentin & Fondy, 1973).…”
Section: Discussionsupporting
confidence: 92%
“…This value is lower than the isoelectric points estimated for rabbit skeletal muscle (6.5), '\, [22] enzymes. It has been reported that the glycerol-3-phosphate oxidoreductase from neoplastic tissues exhibits a lower isoelectric point than that from normal tissue [l].…”
Section: Isoelectric Pointcontrasting
confidence: 63%
“…In a variety of cancer tissues glycerol 3-phosphate dehydrogenase activity is quite low when compared with normal tissue (Boxer & Shonk, 1960;Sacktor & Dick, 1960). The fact that slower hepatoma growth rates are correlated with increased lipid oxidation (Bloch-Frankenthal et al, 1965) and higher glycerol 3-phosphate dehydrogenase activity (Shonk et al, 1965) might suggest a role for the liver enzyme in gluconeogenesis from lipolytically derived glycerol (Warkentin & Fondy, 1973). Its function in gluconeogenesis would be to oxidize glycerol 3-phosphate, formed from glycerol by glycerol kinase, to dihydroxyacetone phosphate which would then be converted into glucose.…”
Section: Discussionmentioning
confidence: 99%